Distribution and dissolution kinetics of biogenic silica in sediments of the northern South China Sea - Ma, Yuwei; Yang, Bin; Zhou, Nan; Huang, Jin; Liu, Su Mei; Zhu, Dongdong; Liang, Wen (Frontiers in Marine Science, 2023)
The dissolution efficiency of sedssimentary biogenic silica (bSiO2) dramatically affects the regeneration of dissolved silicic acid (dSi) at the sediment-water interface, which is a crucial pathway to maintain Si balance and silicic productivity growth in marine environments. We conducted wet alkaline leach and flow-through experiments to explore the dissolution behaviors of sedimentary bSiO2 in the northern South China Sea (NSCS), one of the largest marginal sea continental shelves. The bSiO2 contents of surface sediments were 0.64 - 2.06%, with an average of 1.04 ± 0.35%, varying with isobath water depth. The solubility of bSiO2 in surface sediments ranged from 227 μmol L-1 to 519 μmol L-1, and the dissolution rate constants varied from 0.67 to 1.53 yr-1 under specific conditions in lab incubation. The correlation between the biogenic materials (bSiO2, OC, and TN) revealed a different preservation pattern of bSiO2 in finer (Φ > 5.5) and coarser (Φ< 5.5) sediments. The high concentration of Al in sea water and “Al – detrital – bSiO2” interactions in sediments significantly interfered with the apparent solubility and dissolution dynamics of bSiO2. We combined the regional characteristics (primary production, bottom current, and resuspension-deposition) and the reconstructed dissolution kinetics of bSiO2 explained the mismatch between the surface (diatom biomass)/(total phytoplankton biomass) ratio and the sedimentary bSiO2/OC ratio, and the mismatch between the surface bSiO2 primary productivity and the bSiO2 sediment records in the NSCS. The resuspension-deposition, the higher reconstructed rate constants (0.94 ± 0.13 yr-1), and the dissolution rate (0.20 ± 0.01 yr-1) were responsible for the lower bSiO2/OC ratio (0.45 ± 0.28) at the inner shelf, and the winnowing process at the outer shelf with the lower reconstructed reactivity (0.30 yr-1) and dissolution rate (0.001 yr-1) led to the good preservation of bSiO2 in the upper slope. Furthermore, through the comparison with other sea areas, the relatively lower reactivity (1.12 ± 0.3 yr-1) of bSiO2 in sediments supported the notion that the NSCS sediments may serve as an important silica sink in the world ocean silica cycle.